Fish scale remover machine - Anak Emley, Eryka Respolyn; Abdul Majid, Nor Shamila; Anak Gay, Sharria Sendai; Ya Shak, Aida Syazwani; Hassan, Mohd Fahrul (Penerbit UTHM, 2017)
Laksa, sata and fish ball is a fish based food. Fish belong to groups of coldblooded animals. Fish lives in water, breathe through gills and use fins to move. According to the dictionary, scales are layered flaky skin on the surface of the fish skin. Scales function as a tool of defending them from their enemies. Hardness of fish scales are different depending on the types of fish being used for production